1988
DOI: 10.1007/bf00441414
|View full text |Cite
|
Sign up to set email alerts
|

Sympatho-adrenal response to hypoglycaemia in infants

Abstract: The response of the sympathoadrenal system to hypoglycaemia of different etiology was studied in seven infants, aged 10-189 days. Five infants had hyperinsulinism secondary to nesidioblastosis or to a beta-cell adenoma of the pancreas, one infant had neonatal sepsis due to staphylococcal infection and one infant congenital growth hormone (HGH) and adrenocorticotropic hormone (ACTH) deficiency. In babies with hyperinsulinism, plasma noradrenaline increased from 0.29 +/- 0.03 to 0.61 +/- 0.09 ng/ml (P less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…23 24 This was not supported by a study of human neonates, which demonstrated a marked noradrenergic response to hypoglycaemia. 25 However, in this latter study, hypoglycaemia was induced by abruptly discontinuing high rate glucose infusion and the only SGA infant studied had systemic complications, so the findings may not be applicable to spontaneously occurring hypoglycaemia in otherwise well SGA infants. Increased urinary excretion of catecholamines has been demonstrated for SGA infants during hypoglycaemia but, unfortunately, this particular study did not record plasma catecholamine concentrations.…”
Section: Resultsmentioning
confidence: 77%
“…23 24 This was not supported by a study of human neonates, which demonstrated a marked noradrenergic response to hypoglycaemia. 25 However, in this latter study, hypoglycaemia was induced by abruptly discontinuing high rate glucose infusion and the only SGA infant studied had systemic complications, so the findings may not be applicable to spontaneously occurring hypoglycaemia in otherwise well SGA infants. Increased urinary excretion of catecholamines has been demonstrated for SGA infants during hypoglycaemia but, unfortunately, this particular study did not record plasma catecholamine concentrations.…”
Section: Resultsmentioning
confidence: 77%